LCoS display phase self-calibration method based on diffractive lens schemes. (July 2018) - Zhang, Haolin; Lizana, Angel; Iemmi, Claudio; Monroy-Ramírez, Freddy A.; Márquez, Andrés; Moreno, Ignacio; Campos, Juan
Highlights: We proposed an experimental method to calibrate LCoS displays. We provided a self-calibrating technique based on diffractive lenses schemes. This means the used DOEs are self-generated by the LCoS to be studied. LCoS phase-voltage look-up table, as well as the surface profile, are experimentally obtained with the same (and compact) optical arrangement. As we are dealing with a self-calibrating approach, the technique allows to calibrate the LCoS without the necessity of external optical set-ups. Abstract: An experimental method to calibrate Liquid Crystal on Silicon (LCoS) displays by self-generating lens configurations on the studied device is proposed in this paper. On the one hand, a split-lens is displayed in the LCoS to self-generate an interference pattern from which the phase-voltage curve of the modulator is calculated. On the other hand, a microlens array is displayed on the LCoS, within a same experimental set-up, to implement a Shack-Hartmann (S-H) wavefront sensor, from which the display surface profile is retrieved. Specifically, by means of a feasible set-up, the proposed method allows measuring the deviation from flatness of the LCoS displays as well as to determine the phase-voltage response of phase-only SLMs. Experimental results demonstrate a linear tendency phase-voltage curve that ranges from 0 rad up to ∼6.28 rad, for the used light wavelength. Moreover, by extracting the LCoS phase distribution measured with the S-H configuration, the LCoS surface inhomogeneity is corrected by 95%.